Teaching Pain Management to Student Nurses: A Literature Review - Wijayanti, Ekatrina (Nurse Media Journal of Nursing, 2014)
Purpose: To provide nursing students knowledge of pain prior, during, and post- surgery, recovery and rehabilitation. Methods: Review articles published during 2005 until 2012 that focused on pain assessment and pain management. The databases used in this study were Medline and CINAHL.Results: Postoperative pains need special approach and care. It needs teach patient how to adapt pain, control pain, monitor result of treatment. Conclusion: Nursing students need to learn how to assess pain using appropriate tools for each age level and in patients with special needs. The students also need to learn about pain management including pharmacology and non-pharmacology means and consider pain as the fifth vital sign. As student nurses learn pain assessment, they should be considerate about culture, and different languages that might happen during practical rotations.